2019
DOI: 10.1007/s40263-019-00670-y
|View full text |Cite
|
Sign up to set email alerts
|

Do Vaccines Trigger Neurological Diseases? Epidemiological Evaluation of Vaccination and Neurological Diseases Using Examples of Multiple Sclerosis, Guillain–Barré Syndrome and Narcolepsy

Abstract: This article evaluates the epidemiological evidence for a relationship between vaccination and neurological disease, specifically multiple sclerosis, Guillain-Barré syndrome and narcolepsy. The statistical methods used to test vaccine safety hypotheses are described and the merits of different study designs evaluated; these include the cohort, case-control, case-coverage and the self-controlled case-series methods. For multiple sclerosis, the evidence does not support the hypothesized relationship with hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
13
0
2
Order By: Relevance
“…Sleep quality was reported to worsen during the lockdown by informants, whereas the adults with ASD perceived the opposite outcome. This discrepancy can be explained by analyzing ASD sleep profiles, which are known to show insomnia and sleep phase delay ( Cortese, Wang, Angriman, Masi, & Bruni, 2020 ). During the lockdown period, environmental requirements of time schedules almost completely disappeared, making it unnecessary to get up at a certain time in the morning.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep quality was reported to worsen during the lockdown by informants, whereas the adults with ASD perceived the opposite outcome. This discrepancy can be explained by analyzing ASD sleep profiles, which are known to show insomnia and sleep phase delay ( Cortese, Wang, Angriman, Masi, & Bruni, 2020 ). During the lockdown period, environmental requirements of time schedules almost completely disappeared, making it unnecessary to get up at a certain time in the morning.…”
Section: Discussionmentioning
confidence: 99%
“…Although the interval between first healthcare contact and diagnosis was similar in vaccinated and unvaccinated cases, the former had a shorter interval from onset to first healthcare contact ( Fig 3 ), which, with the short follow-up interval in the earlier study, would have biased upwards the risk estimates. This earlier contact with healthcare may reflect more severe or abrupt onset in vaccinated cases or knowledge of the putative association prompting earlier consultation, even though the first evidence of heightened public interest in narcolepsy (as judged by Google searches in the UK) did not occur until December 2011 [ 15 ]. Despite the lower ORs in the current study, the estimated attributable risk (1 per 34,500 doses) was higher than estimated in the previous study (around 1 in 55,00 doses) because of the inclusion of a substantial number of vaccine-attributable cases with a diagnosis after July 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Antipsychotics are commonly classed as either typical or atypical based upon their potency as dopamine D2 receptor antagonists and their actions on serotonin 5-HT2A receptors [ 26 ]. While several studies, such as the National Institute of Mental Health (NIMH), Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) and sub-studies have not demonstrated a clear and significant difference between second and first generation antipsychotics, at least for schizophrenia, their better safety profile, particularly for extrapyramidal symptoms (EPS), would grant them some actual advantage [ 27 ].…”
Section: Antipsychotic Use In Dementiamentioning
confidence: 99%